Critical Issues in BDNF Val66Met Genetic Studies of Neuropsychiatric Disorders - Tsai, Shih-Jen (Frontiers in Molecular Neuroscience, 2018)
Neurotrophins have been implicated in the pathophysiology of many neuropsychiatric diseases. Brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin in the brain. Its Val66Met polymorphism (rs6265) is a common and functional single-nucleotide polymorphism (SNP) affecting the activity-dependent release of BDNF. Considering the important role of BDNF in brain function, more than 1,100 genetic studies have investigated this polymorphism. Although these studies have reported some encouraging positive findings initially, most of the findings cannot be replicated in following studies. These inconsistencies in BDNF Val66Met genetic studies may be attributed to many factors such as age, sex, environmental factors, ethnicity, genetic model used for analysis, and gene–gene interaction, which are discussed in this review. We also discuss the results of recent studies that have reported the novel functions of this polymorphism. Because many BDNF polymorphisms and nongenetic factors have been implicated in the complex traits of neuropsychiatric diseases, future studies should apply data mining and machine learning techniques to determine the genetic role of BDNF in neuropsychiatric diseases.